Dicionário compartilhado: espaço de criação, resistência e subjetividade - Biazus, Camilla Baldicera (2015)
The general objective of this study is to understand the process of subjectivation of subjects through discourse production, and the construction of meaning for adolescent subjects through the proposal of creating dictionary entries, with drawings and songs, which are part of a shared dictionary that includes the personal and unique story for each participant, as well as it tries to portray the experience of being part of Associação Cuíca. This research has as a starting point to propose the guiding and following of the development of this dictionary by young people who are part of Associação Cuíca (Culture, Inclusion, Citizenship and Arts) that develops cultural activities to the needy population of Santa Maria (RS), prioritizing social inclusion and development of children and adolescents. With the development of these entries it is believed to be possible to analyze the written artistic and creative production of these subjects in order to observe how the production of language as a space of production itself and of possibility of subjectivity in the link with the Other can be constitutive of identity construction. The theoretical background that supports this research is the theory of Discourse Analysis by Pêcheux, which focus on the notions of language, subject and history over others. It is also relevant to point out that as the data collection survey was conducted in Cuíca, this cultural context is considered in the developed practice, as well as in the expected results. For the analysis of discursive materiality collected at first, the entries created by the participants are elected, which are handled in the research so that subsequently these entries can be reassembled from the discursive regularities found among them. Then, the processes of meaning production are described and analyzed with particular emphasis on paraphrases and metaphors as these categories of analysis have been used by Orlandi (2007a, 2012). Furthermore, the analyzed material also serves as a basis for reflection on the concepts of discourse, text, interdiscourse, history and historicity, subject, ideology, unconscious, among others necessary for the development of this study.